Application Of Vat Calculations, PPh Article 22, and PPh Article 23 On the Procurement of Goods/Services: Lagadar Village Office Case Study - Fitriani, Nur; Ramlan, Ramlan; Fajar, Ganjar Nurul; Dianto, Aris (P3M, STIE Pasundan, Bandung, Indonesia., 2024)
The Lagadar Village Office still uses a manual approach to calculate taxes on acquiring goods and services. This condition involves using a calculator and recording the calculations in a notebook. Consequently, the Treasurer frequently made errors while performing computations, whether misclassifying the tax type or inaccurately incorporating the tax rate. Moreover, the requirement to input tax computation data again before printing creates a challenge for the Treasurer in locating the necessary information in the notebook for monthly reporting to the leadership. Hence, there is a requirement for a system that can simplify the Treasurer's task of calculating and summarizing the tax data. This project aims to develop apps that can accurately compute value-added tax, income tax 22, and income tax 23 for the acquisition of goods and services. The employed research methodology is the descriptive research method. The system development method employed is the Object-Oriented Analysis and Design (OOAD) model system development method. The system design employs a web programming language integrated with the Codeigniter framework, utilizes a MySQL database, and employs the Visual Studio Code text editor for development purposes. A research study has led to developing an application at the Lagadar Village Office. This application, designed to calculate Value Added Tax, Article 22 Income Tax, and Article 23 Income Tax for procuring goods and services, is a significant step towards more efficient tax calculations. Its purpose is to assist the Treasurer in efficiently calculating, collecting, recording, and reporting tax calculation data, ensuring accurate and organized records in the system. Research-based recommendations for further development of the application include the creation of an application landing page that provides information on taxation. This will enable application users to stay updated on the latest government regulations pertaining to taxation, particularly for Village Offices. This application not only simplifies the Treasurer's tasks but also ensures accurate and up-to-date tax calculations, instilling a sense of optimism for the future of tax management at the Lagadar Village Office.